Pengaruh Kompetensi, Kompensasi, Konflik Kerja, Serta Stress Kerja Terhadap Kepuasan Kerja Pada Karyawan Wanita di Surakarta - Ananda Alifia Septanesya Rinda Az-Sahra; Ida Ayu Kade Rachmawati Kusasih (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The Purpose Of This Study Was To Determine The Effect Of Competence, Compensation, Work Stress And Work Conflict On Satisfaction Among Female Employees In Surakarta. The Population In This Study Are Female Employees Who Work In The City Of Surakarta. The Sample In This Study Amounted To 97 Respondents, The Sampling Technique Used In This Study Was Purposive Sampling. The Data Analysis Method Used Is The Multiple Regression Test Which Consists Of The F Test, T Test And The Coefficient Of Determination. The Results Of The Simultaneous Study (Test F) Show That There Is A Positive And Significant Influence Between Competence, Compensation, Work Conflict, Job Stress On Job Satisfaction. Partial Test Results (T Test) Obtained Competence Has A Positive And Significant Effect On Job Satisfaction, Compensation Has A Positive And Significant Effect On Job Satisfaction, Work Conflict Has A Positive And Significant Effect On Job Satisfaction, Job Stress Has A Positive And Significant Effect On Job Satisfaction.